Impact Of GSOMIA (General Security Of Military Information Agreement) Treaty Bilateral Military Cooperation Between Japan And South Korea - Ardiyanti, Dwi; Rokhaniyah, Hesti; Dini Danea, Sindi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
North Korea's nuclear missile test launches in the East Asian region create security tensions for regional countries,especially Japan and South Korea, which are geographically very close. Faced with these problems, the two countriesstabilized their national security by carrying out military cooperation as stated in the GSOMIA treaty pact. The GSOMIA Agreement is an agreement made by both countries in response to North Korea's nuclear developments, the agreement allows the two countries to exchange information related to North Korea's nuclear developments supervisedby each country's weapons. However, in the process of ratification of the GSOMIA agreement experienced manyobstacles that came from South Korea's domestic, namely the negative sentiment of the South Korean people towardsJapan related to problems in historical times, this can be evidenced by the delay of the GSOMIA agreement in 2012 during the reign of Lee Myung-bak. In 2016 the GSOMIA agreement was successfully realized by both countries at that time Japan led by Shinzo Abe, South Korea by Park Geun Hye. Of all the processes that have been passed have an impact oneach country, namely the abdication of the South Korean president which is analyzed using the concept of Public Policy and affects the dynamics of bilateral relations between the two countries from decisions made by Japan and South Korea analyzed by the concept of Foreign Policy.